CURCUMA HARVEST ESTIMATION USING GEOSPATIAL INFORMATION - Sunarto, Kris (Badan Informasi Geospasial in Partnership with MAPIN, 2013)
Temulawak or Curcuma (Curcuma xanthorrhiza) is one of prominent herbal medicine that needs to be researchedanddeveloped tomeetboth domestic andexport needs. The development of Curcuma as an agricultural commodity can be done inless fertilelandwith less shade. Curcumais actually among importance herbal medicine commodities; however its price is notstable even considered very low, resulted in a hesitantfor farmersto grow it. Therefore, harvest volume needs to be controlled to anticipate demand at a good price. Habitatof curcuma plantand its productionestimationof a particular area canbe assessedusing geospatial data andinformation. The purposeof this research is tofind out how muchis the optimalpost-harvestproductioninthe studyarea. Method used to obtain the estimationforoptimumposition in this researchis amediummulti-sample value. The result showed that based on demonstration plot (âdemplotâ), the optimum harvest is15.8 tons/hectare/year. Meanwhile, based on classification of land suitability map and the farmerâs capacity, it was estimated that the harvest yielded at the study area was 94.284 tons wet harvest for 5.967 hectares.Â Keywords: Geospatial Information, Curcuma, Herbal Medicine,Optimum Harvest.Â Â ABSTRAKÂ Temulawak atau âCurcumaâ(Curcuma xanthorrhiza) merupakan obat herbal yang perlu diteliti dan dikembangkan untuk memenuhi kebutuhan domestik dan ekspor. Sebagai komoditas pertanian, budidaya temulawak dapat dilakukan di lahan yang kurang subur dengan sedikit naungan. Temulawak sebagai komoditas dibutuhkan, tetapi harga tidak selalu stabil, bahkan terlalu murah, sehingga menyebabkan petani enggan untuk menanamnya.Untuk itu, volume panen harus dikendalikan untuk mendapatkan permintaan pasar dengan harga yang baik. Habitat tanaman dan perkiraan produksi dapat dianalisis menggunakan data dan informasi geospasial. Tujuan penelitian ini adalah untuk mengetahui seberapa besar produksi pasca panen yang optimal pada area penelitian. Metode yang digunakan untuk mendapatkan perkiraan pada posisi optimal adalah menggunakan hasil multi sampel media. Penelitian ini memperlihatkan bahwa berdasarkan demplot yang dihasilkan dari panen optimal adalah 15,8 ton/hektar/tahun. Sedangkan berdasarkan klasifikasi peta penggunaan lahan dan kemampuan petani, diperkirakan bahwa pada area penelitian menghasilkan 94,284 ton panen basah untuk 5,967 hektar lahan.Kata kunci: Informasi Geospatial, Temulawak, Obat Herbal, Panen Optimal.